Mechanical behavior of monolayer MoS2 films with arrayed dislocation defects - Pengsen Zhao; Jing Wang; Zhiqin Wang; Meng Nie (Results in Physics, 2023)
Compared with single and randomly distributed defects, arrayed defects exist widely in the film structure and can be designed artificially to achieve various specific functions. However, the mechanical behavior of transition metal dihalides with dislocation array defects is unclear; this limits their application in new flexible nanodevices. In this study, the strength and fracture properties of monolayer MoS2 films containing 5|7 (S5|7 and Mo5|7) dislocation defects under uniaxial tension were studied by molecular dynamics simulation. The results show that the number of defects, adjacent spacing, and alignment angle affect the critical strain and tensile strength of the monolayer MoS2 films. These results provide a basis for further understanding the mechanical behavior of monolayer MoS2 thin films and provide a theoretical reference for the application of nano-electronic devices based on MoS2.